PERANCANGAN SWING HOIST KAPASITAS 150 KG UNTUK MENGANGKAT SHEET MATERIAL - Riki Effendi; Tofan Megawanto (University of Muhammadiyah Jakarta, 2015)
In the world of handling, the equipment industry is always required to carry out any work activities, one of the sheet material handling tools. With the material handling tools can ease the burden of people in the process of loading and unloading material. Tools There are many kinds of material handling among other cranes, gantry hoist, swing hoist or air hoist, and others. Thus, in this study, the designed begun handling tool that has a lower economic value. For the usage of this tool that works utilizing the principle of force that works on wire rope and bearing due to loading. So the selection of wire rope specifications and bearing very important. From the results of research and calculations of data that are accepted style of wire rope for T = 9894.23 N and styles are acceptable bearing = 490 N axial and radial force = 13905.41 N. Thus it can be concluded from these data that the tool handling swing designed air hoist can be used.